Assessment of the Shellfish Production Areas’ Quality: The Oualidia and Sidi Moussa Lagoons Case - Khbaya, B.; Bouthir, F-Z.; Cherkaoui, R.; Kabiri, E. M. (European Scientific Journal, ESJ, 2023)
Based on European regulation 91/492/EC, Morocco, very early, established legislation with conditions for producing and marketing live bivalve molluscs. In applying this legislation, the National Institute of Fisheries Research (INRH) has set up a system for sanitary monitoring of the marine environment, through which several harvesting areas have been classified while others are in progress. In January 2020, the Oualidia and Sidi Moussa lagoons were categorized respectively in classes B and C with respectively 52.77% of the results, which were between 230 and 4600 MPN E. coli / 100 g of flesh and intravalvular liquid (FIL) and 11.11% of results that fell between 4600 and 46000 MPN E. coli / 100 g FIL. Sidi Moussa lagoon has been classified as a clean area category C since 2006. As a result, the oyster farming activity has been suspended in this area. This incident is a warning sign of the significant weakness of these ecosystems in addressing multiple social and economic challenges. On another side, INRH has sufficient data and tools to progress towards a better optimization of the marine environment sanitary monitoring program management.